2009
DOI: 10.1016/j.jtcvs.2008.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Silver nitrate through flexible bronchoscope in the treatment of bronchopleural fistulae

Abstract: The local application of silver nitrate through a flexible bronchoscopic brush produced a burn and healing process on the mucosa of small bronchopleural fistulae of the central airways, leading to effective and lasting treatment in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
(33 reference statements)
0
24
0
1
Order By: Relevance
“…Several therapeutic options have been reported for the management of bronchopleural fistulas in adults, including independent lung ventilation, 16,17 interventional bronchoscopy, and closure of the bronchopleural fistula with various devices or materials, [18][19][20] but those approaches were technically not possible in our patient. [18][19][20] Our patient was not a candidate for lobectomy, because the necrotizing pneumonia process was not limited to one lobe. [18][19][20] Furthermore, our trial of unilateral lung (left lung) ventilation failed, which left HFOV as the most logical intervention to deal with the failure of conventional ventilation.…”
Section: Teaching Pointsmentioning
confidence: 79%
See 1 more Smart Citation
“…Several therapeutic options have been reported for the management of bronchopleural fistulas in adults, including independent lung ventilation, 16,17 interventional bronchoscopy, and closure of the bronchopleural fistula with various devices or materials, [18][19][20] but those approaches were technically not possible in our patient. [18][19][20] Our patient was not a candidate for lobectomy, because the necrotizing pneumonia process was not limited to one lobe. [18][19][20] Furthermore, our trial of unilateral lung (left lung) ventilation failed, which left HFOV as the most logical intervention to deal with the failure of conventional ventilation.…”
Section: Teaching Pointsmentioning
confidence: 79%
“…[18][19][20] Our patient was not a candidate for lobectomy, because the necrotizing pneumonia process was not limited to one lobe. [18][19][20] Furthermore, our trial of unilateral lung (left lung) ventilation failed, which left HFOV as the most logical intervention to deal with the failure of conventional ventilation.…”
Section: Teaching Pointsmentioning
confidence: 99%
“…So wurden in kleinen retrospektiven Fallserien Fisteln nach Pneumonektomie und Lobektomie erfolgreich durch endoskopische intramurale Unterspritzung von 1 ml 1%igem Silbernitrat ausgeheilt (Boudaya et al 2013;Stratakos et al 2009). So wurden in kleinen retrospektiven Fallserien Fisteln nach Pneumonektomie und Lobektomie erfolgreich durch endoskopische intramurale Unterspritzung von 1 ml 1%igem Silbernitrat ausgeheilt (Boudaya et al 2013;Stratakos et al 2009).…”
Section: Endoskopische Therapie Kleiner Bronchogener Fistelnunclassified
“…14 Nonetheless, bronchoscopic exploration is important as a diagnostic and therapeutic intervention. 19 Silver nitrate acts as a cauterizing agent on the mucosa, leading to coagulation of cellular protein with eschar formation. Hartmann and Rausch 15 and Ratliff et al 16 reported the first successful endobronchial management of BPF using tissue glue and a lead shot, respectively.…”
Section: Surgical Closuresmentioning
confidence: 99%